PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK MEREK TERKENAL BERDASARKAN UNDANG-UNDANG NO. 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS (STUDI KASUS MEREK STRONG VS MEREK STRONG 12 JAM) - Tazkya Salsabila; R Rahaditya (Jurnal Hukum Adigama, 2021)
Trademarks are part of Intellectual Property Rights which can play a role in preventing unfair business competition. Business actors are entitled to legal protection for their trading activities. It is very important to protect well-known brands given the prevalence of brand infringement that occurs, with protection of well-known brands aimed at avoiding the loss of well-known brand holders and protecting consumer confidence in the quality of the well-known brand. However, currently there are still frequent trademark infringements carried out by other parties without rights and without permission to use wellknown brands that have been registered, one of which is the case between Hardwood Private Limited against PT. Unilever Indonesia, Tbk. which will be studied in this research and raises the main issues: How is the legal protection for well-known trademark rights holders based on Law no. 20 of 2016 concerning Brands and Geographical Indications (Case Study of Strong Brand vs Strong Brand 12 Hours) ?. The results of the study indicate that it is true that there have been violations committed by PT. Unilever Indonesia, Tbk. by producing, promoting, marketing similar toothpaste products using the “Strong” brand which results in material and immaterial losses for the well-known brand rights holders, namely Hardwood Private Limited and there is no legal protection for the well-known brand “Strong” owned by Hardwood Private Limited. The author suggests that business actors must prioritize the distinguishing power of the trademark to be registered in order to maintain healthy business competition.